Technology as problem-solving procedures and technology as input-output relations: Some perspectives on the theory of production - Giovanni Dosi; Marco Grazzi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2005)
In this work, inspired by Winter (2006), in fact of vintage 1968, we discuss the relation between three different levels of analysis of technologies, namely as (i) bodies of problem-solving knowledge, (ii) organizational procedures, and (iii) input-output relations. We begin by arguing that the primitive levels of investigation, where the action is, are those which concern knowledge and organizational procedures while in most respects the I/O representation is just an ex post, derived, one. Next, we outline what we consider to be important advances in the understanding of productive knowledge and of the nature and behaviors of business organizations which to a good extent embody such a knowledge. Finally, we explore some implications of such procedural view of technologies in terms of input-output relations (of which standard production functions are a particular instantiation). We do that with the help of some pieces of evidence, drawing both upon incumbent literature and our own elaboration on micro longitudinal data on the Italian industry.
Keywords: 330; theory of production; organizational routines; problem-solving knowledge; production function; micro-heterogeneity; Produktionstheorie; Input-Output-Analyse; Produktionsfunktion; Wissen; Theorie